Best m-term trigonometric approximation for the classes B^r_p,θ of functions of low smoothness - Stasyuk, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We obtain an exact-order estimate for the best m-term trigonometric approximation of the Besov classes B^r_p,θ of periodic functions of many variables of low smoothness in the space L_q, 1 < p ≤ 2 < q < ∞.